Sote-palvelut markkinoilla - tavoitteita, toiveita ja ristiriitoja - Tienhaara, Piia; Rannisto, Pasi-Heikki (Tampere University Press, 2016)
erspective. All in all, this book is an attempt to give the reader a comprehensive understanding of the public health and social services and the markets - markets in which different objectives, expectations and contradictions moderate the discussion and actions. "